PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP RETENSI KARYAWAN (Studi Kasus Pada PT. Selamat Group Kota Bengkulu) - Lancha Durti Sumantri; Khairul Bahrun (UM. Bengkulu, 2022)
This study entitled the effect of compensation and job satisfaction on employee retention at PT. Congratulations Bengkulu City Group. The formulation of the problem in this study is whether the influence of compensation and job satisfaction on employee retention at PT. Congratulations Bengkulu City Group. The purpose of this study was to determine whether the influence of Compensation and Job Satisfaction on Employee Retention at PT. Bengkulu City Seamat Group. This research was conducted on employees of the Production Department of PT. Congratulations Bengkulu City Group. While the time of this research was conducted for 1 month, from January 20, 2021 to February 20, 2021. The population of this study were employees at PT. Selamat Group Kota Bengkulu, while the sample of this study were employees of the Production Department of PT. Congratulations Bengkulu City Group, amounting to 51 people. This means that the sample material uses quantitative methods. With the research test data analysis technique, the results of the study can be concluded that the respondents' perceptions of Compensation (X1) and Job Satisfaction (X2) have an effect on Employee Retention (Y) with multiple linear regression results obtained by the following equation: Y = 10,534 + 0.877 (X_1) + 1.261 (X_2) As well as the coefficient of determination R2 = 0.690 or approximately (690%) through hypothesis testing jointly (simultaneously) and individually (partially) in this study using the f test and t test, Compensation (X1) and Job Satisfaction (X2) on Employee Retention (Y), namely = (53,386> 2,195) and (sig Î± = 0.000 <0.050), so it can be concluded that H_3 is accepted, meaning that the variable compensation (X_1) and job satisfaction (X_2) are simultaneously accepted. ) has a significant effect on Employee Retention (Y).Â Keywords: Compensation and Job Satisfaction Against Employee Retention.